Relationship Between Motion Sickness Susceptibility and Vestibular Test Results - BAL, NİLÜFER (My University, 2024)
Objective: There is no test parameter with high sensitivity and specificity for the diagnosis of motion sickness. The aim of this study was to demonstrate a correlation between vestibular function tests and motion sickness. In addition, our secondary aim is to evaluate the sensitivity of the skull vibration-induced nystagmus test (SVINT) in the diagnosis of motion sickness. Methods: A total of 44 young adults aged 19-25 who had no hearing loss, complaints of dizziness/vertigo, or any diagnosed neurological disease were included. According to the motion sickness susceptibility questionnaire-short form (MSSQ-SF), participants were divided into the motion sickness group (21±1.38 years) and control group (20.5±1.18 years). Mean MSSQ-SF score for the motion sickness group is 78.18±12.2 and for control group 19.09±17.08. Ocular and cervical vestibular evoked myogenic potential tests, SVINT, video head impulse test, and oculomotor tests were performed. Results: The only significant difference between the groups was in n1-p1 amplitudes in the left ocular vestibular evoked myogenic potential test (p=0.014). None of the other parameters differed between the two groups (p>0.05). Conclusions: There was no significant relationship between motion sickness susceptibility and the results of any vestibular function test. Performing diagnostic tests for motion sickness in an environment that creates significant sensory conflict may yield different results. This study contributes to the literature in terms of evaluating the vestibular system using a comprehensive test battery and is the first to use the SVINT test in motion sickness. Keywords: Motion sickness, oculomotor tests, skull vibration induced nystagmus test, vestibular evoked myogenic potentials, video head impulse test

Amaç: Hareket hastalığının tanısı için sensitivite ve spesifitesi yüksek bir test parametresi bulunmamaktadır. Bu çalışmadaki amaç, vestibüler fonksiyon testleri ile hareket hastalığı arasındaki ilişkiyi ortaya koymaktır. Ayrıca, ikincil amacımız kafatası vibrasyonu ile uyarılmış nistagmus testinin (KVUNT) hareket hastalığı tanısındaki duyarlılığını değerlendirmektir. Yöntemler: Çalışmaya işitme kaybı, dizziness/vertigo şikayeti olmayan ve herhangi bir nörolojik hastalığı bulunmayan, yaşları 19-25 arasında değişen toplam 44 genç yetişkin dahil edildi. Hareket hastalığı duyarlılık ölçeği-kısa formuna (HHDÖ-KF) göre katılımcılar hareket hastalığı grubu (21±1,38 yaş) ve kontrol grubu (20,5±1,18 yaş) olarak ikiye ayrıldı. Ortalama HHDÖ-KF puanı, hareket hastalığı grubu için 78,18±12,2 ve kontrol grubu için 19,09±17,08. Bütün katılımcılar oküler ve servikal vestibüler uyarılmış miyojenik potansiyeller, KVUNT, video baş itme testi ve okülomotor testler ile değerlendirildi. Bulgular: Gruplar arasındaki tek anlamlı fark sol oküler vestibüler uyarılmış miyojenik potansiyel testinde n1-p1 amplitüdünde gözlenmiştir (p=0,014). Diğer parametrelerin hiçbirinde iki grup arasında farklılık gözlenmemiştir (p>0,05). Sonuçlar: Hareket hastalığına yatkınlık ile vestibüler fonksiyon test sonuçları arasında anlamlı bir ilişki saptanmamıştır. Önemli duyusal çatışma yaratan bir ortamda hareket hastalığına yönelik tanısal testlerin yapılması farklı sonuçlar doğurabilmektedir. Bu çalışma vestibüler sistemin kapsamlı bir test bataryası ile değerlendirilmesi açısından literatüre katkı sağlamakta olup, KVUNT testinin hareket hastalığında kullanıldığı ilk çalışmadır. Anahtar kelimeler: Hareket hastalığı, okülomotor testler, kafatası vibrasyonu ile uyarılmış nistagmus, vestibüler uyarılmış miyojenik potansiyeller, video baş itme testi
Hareket Hastalığı Duyarlılığı ve Vestibüler Test Sonuçları Arasındaki İlişki
Keywords: Motion sickness; oculomotor tests; skull vibration induced nystagmus test; vestibular evoked myogenic potentials; video head impulse test; Hareket hastalığı; okülomotor testler; kafatası vibrasyonu ile uyarılmış nistagmus; vestibüler uyarılmış miyojenik potansiyeller; video baş itme testi